The dancing monkey [videorecording (DVD)] - O'Neill, Eugene, 1888-1953; Wild, Chandler; Smith, Paige; Forester, Nicole, 1972-; Mossman, John (Random Media, 2024)
In this modern-day adaptation of Eugene O'Neill's "The Hairy Ape," factory line worker Wayne Hughes is the pivotal voter in a union election. Over the course of a day, he confronts the stark realities of being a working person in America.